A144 A MULTIDISCIPLINARY TEAM APPROACH REDUCES PEG SITE COMPLICATIONS. (26th February 2020) - Truax, A M; Reardon, J; Naranian, T; Liu, L W
Abstract: Background: Education provided to patients and their family on how to care for the percutaneous enteroscopic gastrotomy (PEG) tube is limited and varies widely. This can result in site and tube complications, patient discomfort and increased health care utilization. In addition, a lack of practitioner expertise and variability in practice can affect timely treatment of PEG site complications. Continuous Levodopa/Carbidopa Intestinal Gel (LCIG) has become a standard of treatment option for patients with advanced Parkinson Disease. This medication is delivered by a jejunal tube through a PEG tube (PEG-J). Previous studies in this population reported up to 40% of adverse events related to the PEG site. At Toronto Western Hospital, we developed a multidisciplinary team (MDT), involving a gastroenterologist, a clinical nurse specialist (CNS) with expertise in wound and stoma care and the movement disorder clinical nurse to care for the PEG-J in this patient population. Aims: To evaluate the effectiveness of our MDT in reducing PEG site complications and health care utilization. Methods: Consecutive PEG-J patients (n=33) assessed by the MDT between October 2018 and September 2019 were provided standard education on the routine care and maintenance of PEG site complications. The CNS uses a systematic approach to prevent, assess and treat PEG site complications. Before and after the MDT approach, patients were seen the day after the PEG insertion (POD 1), 2 weeks after (titration) and then ad hoc determined by incidence of mild, moderate and severe complications. Post implementation of a MDT approach, patients are seen POD 1, at titration and every 3–6 months during routine visits to the Movement Disorder Clinic. Table 1 outlines classification and suggested treatment based on severity for mild, moderate and severe PEG site complications. Results: The systematic MDT approach completely eliminated all unscheduled, urgent contact to the health care providers by patients who have been assessed and provided education by the MDT (n=33), including new PEG-J (n=7) and previously inserted PEG-J (n=26). 28.5% of new PEG-J patients had moderate or severe site complication rate, 71.5% had mild or no complications. In the group of patients with previously inserted PEG-J tubes, 58% had moderate or severe site complications, 42% had mild or no complications. Conclusions: An interprofessional MDT systematic approach drastically reduces PEG site complications and urgent health care utilization. Patients who receive standardized education pre- and post-insertion have a lower incidence of moderate or severe classification of PEG site complications and unscheduled clinic visits. Funding Agencies: None